KORUPSI DALAM MASYARAKAT TONTONAN - Mubarok, Mubarok (Fakultas Ilmu Politik dan Ilmu Sosial, Universitas Brawijaya, 2011)
In the society of spectacle, the cover, image, and behavior of the actors are emphasized more than the quality of message content. The society of spectacle has been formed since long time ago when spectacling became the inseparable part of human life. Olympiad arena, competition in agility field, and many other spectacles have hypnotized people to stay sit in the front row of the stage. In the rapid development of mass media, the spectales are shifted from real stage to virtual stage with the broadness and rapidity of range in penetrating the boundaries of space and time. In corruption cases, corrupted actors and the spectacling people are united in mass media dynamic work flow. Therefore, corruption has become a new particular stage among the society of spectacle.Key words: Society of spectacle, corruption, mass media